(untitled) (International Journal of Engineering and Computer Science, 2017)
Image segmentation is an integral part of image processing applications like medical images analysis and photo editing. In this paper, we have discussed the most commonly used Image Segmentation techniques using Cellular Automata. The segmentation technique to be chosen depends on the properties of